2019
DOI: 10.1016/j.heliyon.2019.e01332
|View full text |Cite
|
Sign up to set email alerts
|

Green, economic, and partially biodegradable wood plastic composites via enzymatic surface modification of lignocellulosic fibers

Abstract: Lignocellulosic fibers, which obtained from Citrus trees trimmings, were modified with Aspergillus flavus (EGYPTA5) enzymes. The non-modified and the modified lignocellulosic fibers were used with low density polyethylene (LDPE) by melt blending brabender method at 170 °C with different ratio (5, 10 and 20 wt%) to obtain wood plastic composites (WPC). The prepared samples were characterized using Fourier-transformed infrared (FT-IR), Scan Electron Microscope (SEM), and Water vapor transmission rate (WVTR) as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 39 publications
1
36
0
1
Order By: Relevance
“…The mixture was allowed to react till the colour changed from colorless to light orange [2]. The produced selenium nanoparticles were characterized using spectrophotometer (Jenway UV/Visible- 2605 spectrophotometer, England) and transmission electron microscopy as described by Youssef et al [21]. Nano-Se concentrations (0, 20 and 40 ppm) were prepared and applied two times over a period of two weeks as foliar spray on plants after 45 and 60 days, respectively from sowing.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was allowed to react till the colour changed from colorless to light orange [2]. The produced selenium nanoparticles were characterized using spectrophotometer (Jenway UV/Visible- 2605 spectrophotometer, England) and transmission electron microscopy as described by Youssef et al [21]. Nano-Se concentrations (0, 20 and 40 ppm) were prepared and applied two times over a period of two weeks as foliar spray on plants after 45 and 60 days, respectively from sowing.…”
Section: Methodsmentioning
confidence: 99%
“…43 Aer chemical treatment, a large peak for the TK bre appeared at 1060 cm À1 attributed to the ether -C-O-Cgroups. 31 In addition, new characteristic peaks corresponding to the aromatic ring (ph-ring) and its double bond (C]C) were detected at about 780 cm À1 and 1610 cm À1 , respectively. The intensity of the peak which was attributed to hydroxyl groups was reduced in the case of TK bre as shown in Fig.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…Among these studies, some have focused on coupling agents or compatibilizer insertion into the polymer matrix, others on graing or coating of the bre with convenient chemical reagents with the aim of obtaining a hydrophobic material. [28][29][30][31] Sanjay and Yogesha 32 have studied the effect of treatments for jute and kenaf on the morphology and mechanical properties of epoxy composite laminates. Maldas et al 33 have reported that the graing and chemical treatments for sawdust wood residue had a positive effect on the mechanical performance of PS.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the fact that treatment promote wettability of the composite film thereby making them more susceptible to fungi attack. Although, contradicting results have been recently reported by Youssef et al [24] after their investigation on the biodegradable performance of wood plastic composites containing treated and untreated fibers in soil environment. The treated fibers composites showed slightly decrease in biodegradability and this reduction in biodegradability of the treated fiber composites in soil according to the authors was because of removal of undesirable lignocellulosic fibers constituent which made the fiber more compatible with the polymer matrix.…”
Section: Introductionmentioning
confidence: 71%
“…Also, in our previous work [23], groundnut shell powder was used in both treated and untreated form to reinforced recycled polyethylene and the result showed improvement in mechanical properties with evidence of biodegradations. Plant fibers commonly used for the reinforcement of polymer matrix to produce biodegradable polymer composites includes kenaf, jute, flax, sisal, coir, and bamboo [14,[24][25][26][27][28]. Valorization of groundnut shells through its incorporation into polymer matrix will not only add to the list of available lignocellulosic plant fiber fillers but also enhance environmental sanitation thereby promoting healthy ecosystem.…”
Section: Introductionmentioning
confidence: 99%